(untitled) (Aintelia Science Notes, 2022)
This study was conducted to determine yield, yield components and quality parameters of some bread wheat genotypes in Konya-Altinekin conditions during 2020 and 2021 growing seasons. In the experiment, two bread wheat (Triticum aestivum L.) cultivars (Esperia, Konya 2002) and 11 advanced bread wheat lines that were unregistered but purified candidate cultivars were used. The experimental design was a Randomized Complete Block Design with four replications. In this study, grain yield (kg da-1), test weight (kg), thousand kernel weight (g), protein content (%), starch content (%) were evaluated in this research. There were significant differences among cultivars for all evaluated characters with regarding two years. The average of two years was 954.7 kg da-1 in terms of grain yield. According to the average of genotypes, the highest yield was found in the 1010 line with 1062.7 kg da-1, and according to the year x genotype interactions, it was found in the 1010 line with 1148,9 kg da-1 in 2021 as the first group, and in the Konya 2002 variety with 643,9 kg da- 1in 2021 as the latest group.